2011
DOI: 10.1021/op2001673
|View full text |Cite
|
Sign up to set email alerts
|

Process Research on the Asymmetric Hydrogenation of a Benzophenone for Developing the Manufacturing Process of the Squalene Synthase Inhibitor TAK-475

Abstract: A practical synthetic method for the synthesis of the chiral benzhydrol 8, which is the key intermediate of the squalene synthase inhibitor TAK-475 (1), has been developed. The method, via asymmetric hydrogenation of the benzophenone 7, employed Noyori's ruthenium precatalyst of the type [RuCl 2 (diphosphine)(diamine)]. We focused on tuning of the chiral diphosphine, and have discovered a novel ligand, DADMP-BINAP (18c), for the catalyst that has allowed reduction of the operating pressure in the asymmetric hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…[[1e,3-5] In particular, enantioselective additions to diaryl ketones are rare,and to our knowledge none enable addition of an acetylide. [6] We envisioned that enantioselective addition to ac yclic oxocarbenium ion might provide an opportunity for differentiating the faces of ad iaryl-substituted oxocarbenium ion, thus providing an alternative strategy to set a-diaryl, tetrasubstituted stereocenters on oxygen heterocycles.Bytethering one aryl group to the oxygen atom, the otherwise similar aryl substituents are differentiated by freedom of rotation and by their relationship to the oxygen substituents (alkyl versus lone pair). These factors make the geometry of the oxocarbenium ion similar to that of at risubstituted olefin, which has been utilized in powerful enantioselective transformations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[[1e,3-5] In particular, enantioselective additions to diaryl ketones are rare,and to our knowledge none enable addition of an acetylide. [6] We envisioned that enantioselective addition to ac yclic oxocarbenium ion might provide an opportunity for differentiating the faces of ad iaryl-substituted oxocarbenium ion, thus providing an alternative strategy to set a-diaryl, tetrasubstituted stereocenters on oxygen heterocycles.Bytethering one aryl group to the oxygen atom, the otherwise similar aryl substituents are differentiated by freedom of rotation and by their relationship to the oxygen substituents (alkyl versus lone pair). These factors make the geometry of the oxocarbenium ion similar to that of at risubstituted olefin, which has been utilized in powerful enantioselective transformations.…”
mentioning
confidence: 99%
“…Investigation of substituent effects on the 1-aryl group (Ar) showed that useful yields are observed in the formation ortho-, meta-, and para-tolyl-substituted products (4)(5)(6). However,l ow enantioselectivity is observed for the orthotolyl-substituted 6,t hus indicating the limit of steric hindrance.H igher enantioselectivities are obtained with meta substituents.The meta-heteroatom substituents led to the best enantioselectivities (up to 97 % ee; 7-9, 12).…”
mentioning
confidence: 99%
“…Benzoxazepine, which is formed by fusing oxazepine with a benzene ring, is generally considered biologically and pharmaceutically active. , Biological and drug molecules such as amoxicilin, loxapine, (1,2,3,5-tetrahydro-4,1-benzoxazepine-3-yl)­pyrimidines and -purines (with anticancer activity in MCF-7 cells), bozepinib (a potent and selective anticancer compound), and TAK 475 (squalene synthase inhibitor) always contain these structural units (Figure ). Given the complicated structure of benzoxazepine, its synthesis is relatively challenging.…”
mentioning
confidence: 99%
“…[1a,e,2] This approach often relies on enantioselective additions to ketone substrates,which generally require significant differences in the electronic or steric character of their substituents to achieve high ee values. [6] We envisioned that enantioselective addition to ac yclic oxocarbenium ion might provide an opportunity for differentiating the faces of ad iaryl-substituted oxocarbenium ion, thus providing an alternative strategy to set a-diaryl, tetrasubstituted stereocenters on oxygen heterocycles.Bytethering one aryl group to the oxygen atom, the otherwise similar aryl substituents are differentiated by freedom of rotation and by their relationship to the oxygen substituents (alkyl versus lone pair). [6] We envisioned that enantioselective addition to ac yclic oxocarbenium ion might provide an opportunity for differentiating the faces of ad iaryl-substituted oxocarbenium ion, thus providing an alternative strategy to set a-diaryl, tetrasubstituted stereocenters on oxygen heterocycles.Bytethering one aryl group to the oxygen atom, the otherwise similar aryl substituents are differentiated by freedom of rotation and by their relationship to the oxygen substituents (alkyl versus lone pair).…”
mentioning
confidence: 99%
“…Investigation of substituent effects on the 1-aryl group (Ar) showed that useful yields are observed in the formation ortho-, meta-, and para-tolyl-substituted products (4)(5)(6). However,l ow enantioselectivity is observed for the orthotolyl-substituted 6,t hus indicating the limit of steric hindrance.H igher enantioselectivities are obtained with meta substituents.The meta-heteroatom substituents led to the best enantioselectivities (up to 97 % ee; [7][8][9]12).…”
mentioning
confidence: 99%